A comparative study on the bactericidal effectivity of two chemical disinfectants against staphylococcus aureus and pseudomonas aeruginosa - Dizon, Maria Carla H.; Riel, Emary B.; Galban, Angelita (Adviser).
An experimental study was conducted to determine the bactericidal effectivity and anti-corrosive property of the two disinfectants by testing each of them against Staphyloccocus aureus and Pseudomonas aeruginosa. The objectives of this study are to compare the number of colony forming units of Staphyloccocus aureus and Pseudomonas aeruginosa after exposure of the contaminated burs to Disinfectants A and B for 2,`0,20 and 30 minutes and to observe any form of corrosion on burs immersed on the disinfectants for 24 hours. the dental burs were contaminated with the bacteria. They were soaked at the disinfectants at the following time intervals: 2,5,10,20 and 30 minutes. Stimultaneously, the burs were also checked for corrosion. A sample from each was pour-plated in a Nutrient Agar plate and incubated for 24 hours at 37°C. After incubation, no colonies were noted at the plates where the burs were exposed to either of the disinfectants. No corrosion products were also observed. Therefore, there is no significant difference between the bactericidal effectivity of the two disinfectants against, Staphyloccocus aureus and Pseudomonas aeruginosa. There is also no significant difference on the corrosion formation between the two disinfectants.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Disinfection and disinfectants